Innovative Solution for Barriers of Green Logistics in Food Manufacturing Industries - Meraa Divi, Pannirselvan; Syed Radzi, Rahamaddulla; Puteri Fadzline, Muhamad Tamyez; Mohd Ghazali, Maarof; Sorooshian, Shahryar (Research India Publications, 2016)
In this era of technology, logistics has been started to play the crucial part for economic world. Ministry of Natural Resources and Environment (NRE), Malaysia, carbon dioxide emissions from energy usage in industries showed the highest percentage. Most of the manufacturers will face environmental issues because they not aware about green logistics. The study investigated the Green Logistics implementation in food manufacturing industries in Johor Darul Takzim. Three objectives were tested using data generated from research instruments. This thesis analyzes the understanding and awareness of green logistics, determine the barrier that prevent the implementation of green logistics and identify the ways to implement green logistics in food manufacturing industries in Johor Darul Takzim. A total of 47 food manufacturing companies selected to participate in this study from the Federation of Malaysian Manufacturers directory. The questionnaires were sent to a representative of each company. Result of data analysis showed the barrier that prevents food manufacturing companies in Johor Darul Takzim to implement green logistics is Lack of Organization Encouragement. Result showed the best ways to implement green logistics is limiting the number of distribution trips to reduce the carbon footprint.